2003
DOI: 10.1067/mtc.2003.16
|View full text |Cite
|
Sign up to set email alerts
|

The role of proinflammatory cytokines in lung ischemia-reperfusion injury

Abstract: Tumor necrosis factor alpha and interleukin 1beta help regulate the development of lung ischemia-reperfusion injury. They appear to promote injury by altering expression of proinflammatory and anti-inflammatory cytokines and influencing tissue neutrophil recruitment.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

8
99
2
3

Year Published

2004
2004
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 135 publications
(112 citation statements)
references
References 23 publications
8
99
2
3
Order By: Relevance
“…However, the failure of the prior physical training programme to affect lung IR-induced neutrophil influx (as assessed by measurement of MPO activity) is intriguing, especially since TNF-a plays critical roles in the regulation of neutrophil influx following lung IR injury [6,30]. Polymorphonuclear neutrophils are know to release toxic oxygen metabolites, such as superoxide anion, hydroxyl radical and hydrogen peroxide, all of which can produce cellular oxidative damage in pulmonary endothelial and parenchymal cells [31].…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…However, the failure of the prior physical training programme to affect lung IR-induced neutrophil influx (as assessed by measurement of MPO activity) is intriguing, especially since TNF-a plays critical roles in the regulation of neutrophil influx following lung IR injury [6,30]. Polymorphonuclear neutrophils are know to release toxic oxygen metabolites, such as superoxide anion, hydroxyl radical and hydrogen peroxide, all of which can produce cellular oxidative damage in pulmonary endothelial and parenchymal cells [31].…”
Section: Discussionmentioning
confidence: 99%
“…The present data show that the number of mononuclear and polymorphonuclear cells in trained rats (86¡3610 6 Measurement of right lung MPO activity was carried out in order to evaluate neutrophil infiltration into lung tissue. Figure 1b shows that lung IR caused a significant increase in MPO activity compared with the sham group that remained unaltered in trained rats.…”
Section: Peripheral Leukocyte Countsmentioning
confidence: 99%
See 1 more Smart Citation
“…Proinflammatory cytokines, such as IL-1, tumor necrosis factor ␣ (TNF-␣), and IL-6 play a pivotal role in IRI and cellular trafficking (49). These effects are modulated by the elaboration of antiinflammatory cytokines IL-4 and IL-10 (50).…”
Section: Early Graft Dysfunctionmentioning
confidence: 99%
“…In addition to serving as chemotactic factors, C-C chemokines can modulate cytokine production, adhesion molecule expression, and mononuclear cell proliferation. Krishnadasan et al demonstrated that TNF-α and IL-1β promote lung IR injury likely by altering the expression of other pro-inflammatory cytokines and by influencing neutrophil recruitment (Krishnadasan, et al, 2003). Antibodies to TNF-α, IFN-γ, and MCP-1 have been utilized to demonstrate the importance of these mediators in lung IR injury (Eppinger, et al, 1997).…”
Section: Cytokines and Chemokinesmentioning
confidence: 99%